Growing impact of sialic acid-containing glycans in future drug discovery. (May 2023) - Bose, Priyanka; Jaiswal, Manoj K.; Singh, Sumit K.; Singh, Rakesh K.; Tiwari, Vinod K.
Abstract: In nature, almost all cells are covered with a complex array of glycan chain namely sialic acids or nuraminic acids, a negatively charged nine carbon sugars which is considered for their great therapeutic importance since long back. Owing to its presence at the terminal end of lipid bilayer (commonly known as terminal sugars), the well-defined sialosides or sialoconjugates have served pivotal role on the cell surfaces and thus, the sialic acid-containing glycans can modulate and mediate a number of imperative cellular interactions. Understanding of the sialo-protein interaction and their roles in vertebrates in regard of normal physiology, pathological variance, and evolution has indeed a noteworthy journey in medicine. In this tutorial review, we present a concise overview about the structure, linkages in chemical diversity, biological significance followed by chemical and enzymatic modification/synthesis of sialic acid containing glycans. A more focus is attempted about the recent advances, opportunity, and more over growing impact of sialosides and sialoconjugates in future drug discovery and development. Graphical abstract: Image 1 Highlights: Sialic acids, referred as 'terminal sugars' play pivotal role on cell surfaces and can modulate a number of imperative cellular interactions in biological processes. Chemoenzymatic route for the development of diverse range of biologically relevant sialic acids-linked glycans is presented. Click chemistry-mediated triazole-appended glycohybrids and their growing impact in drug development is highlighted. This tutorial review highlights the recent advances and challenges at the interface of chemistry and biology of sialic acids in order to find out their scope in drug discovery and development.